Cellulose Aerogel with Zinc Oxide for Wound Dressing Application - Salsabila, Cholivia Hayyu; Purnama Sari, Nur Shiyama; Setyawan, Heru; Widiyastuti, W; Putri Suari, Ni Made Intan (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2024)
This research aim is to determine the performance of coconut fiber-based cellulose aerogel impregnated with zinc oxide for wound dressing applications. Cellulose is an alternative material in aerogel synthesis. Cellulose aerogel is the latest third generation in aerogel research which has attracted much attention due to its good prospects, especially in terms of environmental friendliness and price effectiveness. The synthesis of cellulose aerogel begins with the cellulose purification stage through delignification and bleaching, followed by the addition of NaOH-urea solution, freeze drying and the final stage is impregnation with zinc oxide. Zinc oxide (ZnO) has nontoxic, safe and biocompatible properties and functions as an antibacterial agent. The cellulose/ZnO aerogel formed was subjected to performance tests including analysis of porosity, water absorption capacity, water vapor permeability and antibacterial tests. Based on research that has been carried out, it was found that coconut fiber-based cellulose aerogel impregnated with ZnO has a good potential as a wound dressing application. The porosity of the resulting cellulose aerogel can reach above 90% with high water absorption capacity and has a water vapor permeability which increases with increasing cellulose concentration. Antibacterial tests show that the cellulose/ZnO aerogel has good antimicrobial characteristics.